1978
DOI: 10.1084/jem.148.5.1137
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties of Entamoeba: increased rates of human erythrocyte phagocytosis in pathogenic strains.

Abstract: Amebiasis is one of the most frequent protozoan infections of man, because an estimated 10% of the world population is affected (1). The disease is caused by Entamoeba histolytica, the only Entamoeba known to be pathogenic for humans. The motile form or trophozoite can live in the intestinal lumen as a harmless commensal, but occasionally, and for unknown reasons, it can invade the colonic mucosa giving rise to amebic dysentery and subsequently to liver abscesses (2). In addition to E. histolytica, nonpathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(50 citation statements)
references
References 13 publications
0
47
1
1
Order By: Relevance
“…The specificity of this finding was further reduced when it was demonstrated that in some patients E. dispar also contains RBCs (80). In vitro studies have also confirmed the ability of E. dispar to ingest RBCs (191). In one study, the specificity of E. histolytica/E.…”
Section: Microscopymentioning
confidence: 84%
“…The specificity of this finding was further reduced when it was demonstrated that in some patients E. dispar also contains RBCs (80). In vitro studies have also confirmed the ability of E. dispar to ingest RBCs (191). In one study, the specificity of E. histolytica/E.…”
Section: Microscopymentioning
confidence: 84%
“…Erythrophagocytosis of E. histolytica was assayed as previously described (47). Briefly, trophozoites (10 4 cells) of HM-1:IMSS were exposed to 100 g of each Fab at 37°C for 30 min and then washed with ice-cold PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Amebic cytotoxicity and phagocytic ability both correlate with parasite virulence (21,23,24,26,31,35). Indeed, the observation of ingested host cells is the only characteristic on light microscopy that distinguishes E. histolytica from the nonpathogenic intestinal commensal organism Entamoeba dispar (16).…”
mentioning
confidence: 99%